Prediction of individual characteristics and lactation facilities in the workplace on the sustainability of working mother’s exclusive breastfeeding - Siti Rahmah Hidayatullah Lubis; Indri Hapsari Susilowati (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: Working mothers are more likely than stay-at-home mothers to discontinue breastfeeding earlier. The province of Banten has a low rate of exclusive breastfeeding coverage. The government issued several regulations to address the challenges and barriers in the workplace to continue exclusive breastfeeding. The research aims to predict the influence of individual characteristics and lactation facilities in the workplace on the sustainability of exclusive breastfeeding for working mothers. Method: This study uses a quantitative approach with a cross-sectional design. 65 survey respondents were given online questionnaires. Mothers who work in the Banten area, in speciï¬c, are currently or have previously breastfed their babies aged 6-24 months. The study was carried out in July 2022. The quantitative analysis used logistic regression to identify factors that significantly relate to the sustainability of exclusive breastfeeding. Result: The study's findings indicate that the knowledge variable of working mothers has a significant effect, with a p-value of 0.040 and an Odds Ratio of 5.564, implying that working mothers with poor knowledge are 5.5 times more likely to discontinue exclusive breastfeeding than working mothers with good knowledge. Conslusion: Develop an intervention model in the workplace that provides education about dairy milk management.